Finitely represented dyadic sets and their multielementary representations - Belousov, K. I.; Nazarova, L. A.; Roiter, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain the direct reduction of representations of a dyadic set S such that |Ind C(S)| < ∞ to the bipartite case.